Antioxidant Role of Kaempferol in Prevention of Hepatocellular Carcinoma - Nidhi Sharma; Subhrajit Biswas; Noura Al-Dayan; Alaa Saud Alhegaili; Maryam Sarwat (MDPI AG, 2021)
Reactive oxygen species (ROS) are noxious to cells because their increased level interacts with the body's defense mechanism. These species also cause mutations and uncontrolled cell division, resulting in oxidative stress (OS). Prolonged oxidative stress is responsible for incorrect protein folding in the endoplasmic reticulum (ER), causing a stressful condition, ER stress. These cellular stresses (oxidative stress and ER stress) are well-recognized biological factors that play a prominent role in the progression of hepatocellular carcinoma (HCC). HCC is a critical global health problem and the third leading cause of cancer-related mortality. The application of anti-oxidants from herbal sources significantly reduces oxidative stress. Kaempferol (KP) is a naturally occurring, aglycone dietary flavonoid that is present in various plants (Crocus sativus, Coccinia grandis, Euphorbia pekinensis, varieties of Aloe vera, etc.) It is capable of interacting with pleiotropic proteins of the human body. Efforts are in progress to develop KP as a potential candidate to prevent HCC with no adverse effects. This review emphasizes the molecular mechanism of KP for treating HCC, targeting oxidative stress.